Renalasa sérica y alfa amilasa salival en pacientes con diabetes mellitus tipo 2 - Escudero Hernández, Libertad (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
México holds the sixth place worldwide in Diabetes Mellitus type 2. Renalase (RNLS) is a hormone of recent discovery, it metabolizes the circulating catecholamines. Salivary alpha amylase is related to the carbohydrate digestion; both have been proposed as sympathetic activity markers. The target of this work was to evaluate the RNLS serum concentration, sAA and catecholamines in patients with DM2 compared with three other groups. In a prospective, transversal, comparative and clinical screening, 163 individuals were analyzed, arranged in three groups. Group 1: 14 apparently healthy individuals (95); Group 2: 43 with metabolic syndrome (MS) components (26%); Group 3: 93 patients with DM2 (57%) and Group 4: 13 (8%) with diabetic nephropathy in hemodialysis. All the results were compared with group 1. The statistical analyses were made through central tendency and dispersion tests, Pearson correlation in order to establish association and risk; ANOVA to determinate the difference between the means when comparing more than three groups. With a lower value than 0.05, p was considered as significant. The patient with chronic kidney disease (CKD) has higher catecholamine concentrations compared to the other groups. Renalase was lower in patients with CKD and healthy controls ( = 9.2 ± 2.7 DE vs 10.4 ± 2.4 respectively).

México ocupa el sexto lugar mundial de Diabetes mellitus tipo 2 (DM2). Renalasa (RNLS) es una hormona de reciente descubrimiento, metaboliza las catecolaminas circulantes. Alfa amilasa salival (sAA), se relaciona con la digestión de los carbohidratos; ambas han sido propuestas como marcadores de la actividad simpática. El objetivo del trabajo fue evaluar las concentraciones de RNLS sérica, sAA y catecolaminas en pacientes con DM2 en comparación con otros tres grupos. En un estudio prospectivo, transversal, comparativo y clínico se analizaron a 163 individuos, agrupados en 4 grupos. Grupo 1: 14 sujetos sanos aparentemente (95); Grupo 2: 43 con componentes del Síndrome metabólico (SM), (26%); Grupo 3: 93 pacientes con DM2 (57%); y Grupo 4: 13 (8%) con nefropatía diabética en hemodiálisis. Todos los resultados fueron comparados con el grupo 1. El análisis estadístico se llevó a cabo mediante pruebas de tendencia central y dispersión, correlación de Pearson para establecer asociación y riesgo; ANOVA para determinar diferencia entre las medias al comparar más de tres grupos. Se consideró a p como significativa con un valor menos a 0.05. Los pacientes con ERCT tuvieron concentraciones mayores de Catecolaminas en relación a los otros grupos. Renal DE vs 10.4 ± 2.4 respectivamente).
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias de la Salud
Keywords: info:eu-repo/classification/cti/3; FCMB-M-2015-1398; Renalasa; Alfa amilasa salival; Diabetes mellitus 2; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2968